Isolation and characterization of the cytotoxicity, intracellular bioactivity and mechanism of antimycobacterial action of Euclea natalensis-derived naphthoquinones - Lall, Namrita (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 2010.